(3TQM bUjOI cYH Hf RgjQs - (3GdCfUGQj GdeUQj, CHh eMeO, GHf gTGe, LeGd GdOjf, YHOGddg Hf jhSa Hf CMeO Hf YHOGddg, J (B761 (3g`s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdefYe HEdgGe GdMeO dYHjOg MeOG ehGajG dfYeg(B...(3aEfj ehQO aj gPG GdcJGH bUjOI cYH Hf RgjQ(B...(3heQOa cd HjJ efgG HTQM eG jTcd ef dZJg hEYQGHg(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG CKfGA TQM GdHjJ (B( (3dG jbY GdWYf EdG aj fMhQge(B***(3heG dge Yf MjGV GdehJ Jgdjd(B) (3bhdg(B: ...(3Jgdjd eUOQ gdd Yf GdTjA EPG JCNQ Yfg jbhd dG jJCNQhf Yf MjGV GdehJ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B147s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B305s
(3cTa GdXfhf(B:(3L(B2(3,U(B1329s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdCOHs